Identification and Characterization of a Periplasmic Aminoacyl-phosphatidylglycerol Hydrolase Responsible for Pseudomonas aeruginosa Lipid Homeostasis - Arendt, Wiebke (American Society for Biochemistry and Molecular Biology, 2013)
Specific aminoacylation of the phospholipid phosphatidylglycerol (PG) with alanine (or with lysine) was shown to render various organisms less susceptible to antimicrobial agents and environmental stresses. In this study, we make use of the opportunistic pathogen Pseudomonas aeruginosa to decode ORF PA0919-dependent lipid homeostasis. Analysis of the polar lipid content of the deletion mutant ΔPA0919 indicated significantly enlarged levels of alanyl-PG. The resulting phenotype manifested an increased susceptibility to several antimicrobial compounds when compared with the wild type. A pH-dependent PA0919 promoter located within the upstream gene PA0920 was identified. Localization experiments demonstrated that the PA0919 protein is anchored to the periplasmic surface of the inner bacterial membrane. The recombinant overproduction of wild type and several site-directed mutant proteins in the periplasm of Escherichia coli facilitated a detailed in vitro analysis of the enzymatic PA0919 function. A series of artificial substrates (p-nitrophenyl esters of various amino acids/aliphatic acids) indicated enzymatic hydrolysis of the alanine, glycine, or lysine moiety of the respective ester substrates. Our final in vitro activity assay in the presence of radioactively labeled alanyl-PG then revealed hydrolysis of the aminoacyl linkage, resulting in the formation of alanine and PG. Consequently, PA0919 was termed alanyl-PG hydrolase. The elucidated enzymatic activity implies a new regulatory circuit for the appropriate tuning of cellular alanyl-PG concentrations.